Prevalence of Hyperkalaemia in Chronic Haemodialysis Patients - Mathew Barnd; Daniel Yreck (Newinera Publisher, 2022)
Haemodialysis patients are more likely to suffer from hyperkalaemia than the general population. It puts them at danger of a fatal accident. In haemodialysis, it is not part of the standard examinations. The purpose of our study was to find out how common it was among individuals on long-term dialysis. Our research was cross-sectional in nature. Participants had to have been on haemodialysis for at least two months and be willing to participate in the research. Before the start of their first and second weekly dialysis sessions, we did a clinical examination, blood potassium, sodium, and ionized calcium tests, and an electrocardiogram in each of them. 88 patients were chosen for the study. Before the first dialysis session began, 38.7 percent of patients had hyperkalaemia, and 17 percent had it before the second. In three cases, the blood potassium level was determined to be at least 7.5 mEq / l, indicating that the patient was suffering from a condition known as paresis. Hyperkalaemia is associated with a tall T wave on the ECG in two circumstances. Although hyperkalaemia is widespread in our dialysis patients, its clinical and electrocardiographic symptoms are less so.